Thompson hemiarthroplasty versus modular unipolar implants for patients requiring hemiarthroplasty of the hip: A systematic review of the evidence. Issue 8 (August 2017) - Sims, A. L.; Farrier, A. J.; Reed, M. R.; Sheldon, T. A.
Abstract : Objectives: The objective of this study was to assess all evidence comparing the Thompson monoblock hemiarthroplasty with modular unipolar implants for patients requiring hemiarthroplasty of the hip with respect to mortality and complications. Methods: A literature search was performed to identify all relevant literature. The population consisted of patients undergoing hemiarthroplasty of the hip for fracture. The intervention was hemiarthroplasty of the hip with a comparison between Thompson and modular unipolar prostheses. Pubmed, Embase, CINAHL, Web of Science, PROSPERO and the Cochrane Central Register of Controlled Trials. The study designs included were randomised controlled trials (RCTs), well designed case control studies and retrospective or prospective cohort studies. Studies available in any language, published at any time until September 2015 were considered. Studies were included if they contained mortality or complications. Results: The initial literature search identified 4757 items for examination. Four papers were included in the final review. The pooled odds ratio for mortality was 1.3 (95% confidence Interval 0.78 to 2.46) favouring modular designs. The pooled odds ratio for post-operative complications was 1.1 (95% CI 0.79 to 1.55) favouring modular designs. Outcomes were reported at 12 or six months. These papers all contained potential sources of bias and significant clinical heterogeneity. Conclusion: The current evidence comparing monoblock versus modular implants in patients undergoing hemiarthroplasty is weak. Confidence intervals around the pooled odds ratios are broad and incorporate a value of one. Direct comparison of outcomes from these papers is fraught with difficulty and, as such, may well be misleading. A well designed randomised controlled trial would be helpful to inform evidence-based implant selection. Cite this article : A. L. Sims, A. J. Farrier, M. R. Reed, T. A. Sheldon. Thompson hemiarthroplasty versus modular unipolar implants for patients requiring hemiarthroplasty of the hip: A systematic review of the evidence. Bone Joint Res 2017;6:–513. DOI: 10.1302/2046-3758.68.BJR-2016-0256.R1.